Pelaksanaan Asesmen Risiko dan Asesmen Kebutuhan Terhadap Narapidana Narkotika Di Lapas Narkotika Kelas III Sawahlunto - Ahmad Pajri; Nelwitis (Fakultas Hukum Universitas Andalas, 2024)
Carrying out risk and needs assessments as regulated in Article 36 Paragraph 4 of Law Number 22 of 2022 concerning Corrections is related to the need for guidance, the risk of running away, the risk of danger to other people and the mental physical and psychological health of correctional inmates. For inmates at Lapas Narkotika Kelas III Sawahlunto, this assessment is carried out by the Bapas Klas I Padang. The analysis and discussion of this research uses an empirical juridical approach using field research and interviews with informants. The research results showed that risk and needs assessments were carried out using several instruments such as the Prisoner Placement Screening Instrument (ISPN), the Indonesian Recidivism Risk Assessment Instrument (RRI) and the Criminogenic Needs Assessment. The results of the assessment are recommendations in nature but should be implemented by the prison in order to determine the prisoner development program. The obstacles faced in carrying out this risk and needs assessment are related to the distance between the Bapas Klas I Padang and the Lapas Narkotika Kelas III Sawahlunto, the lack of budget and lack of coordination, as well as the inactivity of the Bapas Post which causes the wide working area of ​​the Bapas Klas I Padang